2022
DOI: 10.1021/acs.inorgchem.1c03201
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phonons and Oxygen Vacancies in Non-Cubic SrVO3

Abstract: Combining neutron diffraction with pair distribution function analysis, we have uncovered hidden reduced symmetry in the correlated metallic d 1 perovskite, SrVO3. Specifically, we show that both the local and global structures are better described using a GdFeO3 distorted (orthorhombic) model as opposed to the ideal cubic ABO3 perovskite type. Recent reports of imaginary phonon frequencies in the density functional theory (DFT)-calculated phonon dispersion for cubic SrVO3 suggest a possible origin of this obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…Unsurprisingly, no soft modes were observed in any of the BZ paths considered here. This is in line with other theoretical treatments [39,41], although we note that Hossain et al [40] did find soft modes, which we suspect to be artefactual.…”
Section: Phonon Dispersions and Thermodynamic Properties Of Cubic Srvosupporting
confidence: 93%
See 3 more Smart Citations
“…Unsurprisingly, no soft modes were observed in any of the BZ paths considered here. This is in line with other theoretical treatments [39,41], although we note that Hossain et al [40] did find soft modes, which we suspect to be artefactual.…”
Section: Phonon Dispersions and Thermodynamic Properties Of Cubic Srvosupporting
confidence: 93%
“…Comparison of the predicted partial densities of states (PDOS) of pristine and oxygen-deficient SrVO 3 revealed that the excess electrons resulting from oxygen vacancies are redistributed to the neighboring V 4+ t 2g states, a conclusion consistent with Bader and charge density difference (CDD) analysis. Phonon dispersions and vibrational density of states (VDOS) analysis confirmed the dynamic stability of cubic SrVO 3 , which agrees with previous experimental and theoretical observations [39,41]. Comparison of the vibrational properties of pristine and defective SrVO 3 suggests that ionic contributions to the VDOS are strongly affected by the oxygen vacancies, and thereby the temperature-dependent reduction properties of SrVO 3−δ .…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations